Seeking justice, equity, diversity and inclusion in pediatric nephrology - Seo-Mayer, Patricia; Ashoor, Isa; Hayde, Nicole; Laster, Marciana; Sanderson, Keia; Soranno, Danielle; Wigfall, Delbert; Brown, Denver (Frontiers in Pediatrics, 2022)
Inequity, racism, and health care disparities negatively impact the well-being of children with kidney disease. This review defines social determinants of health and describes how they impact pediatric nephrology care; outlines the specific impact of systemic biases and racism on chronic kidney disease care and transplant outcomes; characterizes and critiques the diversity of the current pediatric nephrology workforce; and aims to provide strategies to acknowledge and dismantle bias, address barriers to care, improve diversity in recruitment, and strengthen the pediatric nephrology community. By recognizing historical and current realities and limitations, we can move forward with strategies to address racism and bias in our field and clinical practices, thereby cultivating inclusive training and practice environments.